Human Resource Practices for Achieving Organizational Performance with reference to Demographic Analysis - Gautam, Tara Prasad (Nepal Journal of Multidisciplinary Research, 2022)
The purpose of this study would be how demographic variables affect human resource practices and organizational effectiveness. Pharmacies Nepal, This research also looks at how applicable gender-based perceptions are to HRM practices. Nepalese pharmaceutical firms Primary and secondary sources were used to perform this research. Human resource procedures are critical to the organization's continued competitiveness in the marketplace. To achieve the desired performance of the organization, these human resource practices must be managed successfully. Human resources must be managed and adapted on a regular basis. Organizational performance is becoming increasingly crucial, particularly in a competitive and dynamic market. Different indicators are used to assess organizational performance. It ensures the organization's ability to remain competitive in a global marketplace. In most cases, human resources are used to execute performance indicators.